Longitudinal translocator protein-18 kDa–positron emission tomography imaging of peripheral and central myeloid cells in a mouse model of complex regional pain syndrome. Issue 9 (September 2019) - Cropper, Haley C.; Johnson, Emily M.; Haight, Elena S.; Cordonnier, Stephanie A.; Chaney, Aisling M.; Forman, Thomas E.; Biswal, Anjali; Stevens, Marc Y.; James, Michelle L.; Tawfik, Vivianne L.
Abstract : Abstract: Complex regional pain syndrome (CRPS) is a severely disabling disease characterized by pain, temperature changes, motor dysfunction, and edema that most often occurs as an atypical response to a minor surgery or fracture. Inflammation involving activation and recruitment of innate immune cells, including both peripheral and central myeloid cells (ie, macrophages and microglia, respectively), is a key feature of CRPS. However, the exact role and time course of these cellular processes relative to the known acute and chronic phases of the disease are not fully understood. Positron emission tomography (PET) of translocator protein-18 kDa (TSPO) is a method for noninvasively tracking these activated innate immune cells. Here, we reveal the temporal dynamics of peripheral and central inflammatory responses over 20 weeks in a tibial fracture/casting mouse model of CRPS through longitudinal TSPO-PET using [ 18 F]GE-180. Positron emission tomography tracer uptake quantification in the tibia revealed increased peripheral inflammation as early as 2 days after fracture and lasting 7 weeks. Centralized inflammation was detected in the spinal cord and brain of fractured mice at 7 and 21 days after injury. Spinal cord tissue immunofluorescent staining revealed TSPO expression in microglia (CD11b+) at 7 days but was restricted mainly to endothelial cells (PECAM1+) at baseline and 7 weeks. Our data suggest early and persistent peripheral myeloid cell activation and transient central microglial activation are limited to the acute phase of CRPS. Moreover, we show that TSPO-PET can be used to noninvasively monitor the spatiotemporal dynamics of myeloid cell activation in CRPS progression with potential to inform disease phase–specific therapeutics. Abstract : Supplemental Digital Content is Available in the Text.Longitudinal positron emission tomography of translocator protein-18 kDa revealed early central, and persistent peripheral, myeloid activation in a mouse tibial fracture model of complex regional pain syndrome.